Potensi Hidden Canyon Beji Guwang Sebagai Daya Tarik Wisata Alam di Desa Guwang Kecamatan Sukawati, Gianyar - Filia Eka Risti; I Putu Anom (JURNAL DESTINASI PARIWISATA, 2017)
Potential Beji Guwang Hidden Canyon with the beauty of the river that flanked by rocks cliff, this natural beauty can be enjoyed by doing tracking to find a good spot to take photo. Beji guwang hidden canyon present a unique view of nature to tourist that can not be find in another place in bali, this is why I choose this topic “Potential of Beji guwang hidden canyon as a nature tourist attraction in Guwang village Sukawati district, Gianyar” The type and data resources that used in this research are qualitative data, primer and secondary data. This collecting data method was done by observation, in depth interview and documentation by research instrument by in form of interview guide lines. Data analysis that been use was interactive data analysis by use 4A component and SWOT analysis matriks to extract and analysis the potential in Beji Guwang Hidden Canyon The result of the research show that the potensial Beji guwang hidden canyon has is quiet big because having more than one nature tourist attraction. In addition of a tourism activity in Beji Guwang Hidden canyon getting a good respond from the local government and local people. Beji Guwang Hidden Canyon has a big potential, even though there are lack of knowledge in management and development that must be completed. So that the development of Beji Guwang Hidden Canyon can have a good progress. Keywords:Potential, Canyon, Nature Attraction